(untitled) (Bangladesh Journal of Botany, 2020)
The MYB gene family is one of the most widespread plant transcription factor (TF) families, and MYB TFs play key roles in plant development, hormone signal transduction, disease resistance, abiotic stress tolerance and secondary metabolism. Recently, many MYBs have been characterized in various plants. However, little is known about the MYBs involved in secondary metabolite biosynthesis in Dimocarpus longan Lour. (D. longan). Based on transcriptome data profiling (Accession number: SRP155595), 35 MYBs from D. longan (DlMYBs) were identified. On the basis of their physicochemical properties, phylogenetic relationships, conserved motifs, and tissue-specific expression profiles these Dimocarpus longan MYBs (DlMYBs) were analyzed. Fifteen motifs in DlMYBs using MEME were found and a phylogenetic tree analysis showed that the DlMYBs identified here were divided into three groups. Group A contained the greatest number (25) of DlMYBs, followed by group B (6) and group C (4). Quantitative real time PCR (qRT-PCR) analysis demonstrated that, of the 35 MYBs studied DlMYB-12 and DlMYB-22 showed large differences in tissue-specific expression, with both MYBs showing very high expression in leaf tissue. These results lay the foundation for further studies of the biosynthesis of secondary metabolites in D. longan and further highlight the importance of MYB TFs in plants.